Erratum - Gamze Fışkın Siyahtaş; Mukaddes Turan Miral (Ebelik ve Sağlık Bilimleri Dergisi)
The title of the study titled “Endocrine Disruptors as Perspective of Pregnant School Educators: A Qualitative Study” published in the June 2024 issue of the Journal of Midwifery and Health Sciences was mistakenly written in the citation section as “Cite this article: Turan Miral, M., Fışkın Siyahtaş G., (2024). Endocrine Disruptors as Perspective of Pregnant School Educators: A Qualitative Study. Journal of Midwifery and Health Sciences, 7(1):317‐327.” and the number information is stated as “1”.The correct statement should be “Cite this article: Turan Miral, M., Fışkın Siyahtaş G., (2024). Endocrine Disruptors as Perspective of Pregnant School Educators: A Qualitative Study. Journal of Midwifery and Health Sciences, 7(2), 317‐327.”